Natural history and outcomes in drug‐induced autoimmune hepatitis. Issue 3 (25th May 2015) - Yeong, Tian T.; Lim, Kok H. J.; Goubet, Stephanie; Parnell, Nick; Verma, Sumita
Abstract : Aim: Drug‐induced autoimmune hepatitis (DIAIH) remains poorly characterized. Our aim was to assess natural history and outcomes in DIAIH. Methods: This was a retrospective cohort study. Results: Eighty‐two patients with autoimmune hepatitis (AIH) were identified, 11 (13.4%) with DIAIH, implicated drugs being nitrofurantoin ( n  = 4), statins ( n  = 4), herbal remedies ( n  = 2) and diclofenac ( n  = 1). Female sex, acute onset, elevated serum globulins/immunoglobulin G, fibrosis stage (Ishak), cirrhosis at onset, moderate–severe portal inflammation, interface and lobular hepatitis, remission, relapse and poor outcome were similar in those with DIAIH and AIH ( P  > 0.05). The former were however more likely to be aged 60 years or more and take longer to relapse on immunosuppression discontinuation ( P  = <0.05). On Kaplan–Meier analysis, probability of poor outcome was similar in those with DIAIH and AIH (log–rank test, 0.339). On comparing those with ( n  = 4) and without nitrofurantoin ( n  = 7) DIAIH, the former were older, had longer duration of drug use prior to DIAIH diagnosis, higher fibrosis stage and were less likely to relapse upon immunosuppression discontinuation. Conclusion: Approximately 15% of patients with AIH have DIAIH with similar outcomes, although the latter are older with a propensity for late relapse, mandating long‐term follow up.